Hubungan Faktor Gaya Hidup Terhadap Kejadian Hipertensi Pada Penduduk Usia ≥ 18 Tahun Di Kabupaten Bekasi, Jawa Barat (Analisis Data Riskesdas 2018) - Tika Rahma Maudyta (2022)
The prevalence of hypertension in Bekasi Regency reached 32.8% in 2018. Hypertension in Bekasi Regency is included in the 10 most common disease patterns in puskesmas and the 10 highest causes of death. Bekasi Regency is an urban area where the lifestyle of the people shifts to an unhealthy lifestyle that can cause hypertension. The purpose of this study was to see the relationship between lifestyle factors (consumption of high-salt foods, consumption of fatty foods, smoking habits, and physical activity) on the incidence of hypertension in the population aged 18 years in Bekasi Regency, West Java Province from Riskesdas 2018 data. This study is an observational analytic with a cross-sectional study design and uses secondary data from Riskesdas 2018. The research sample is 1309 people with a total sampling technique. The data analysis used is Chi-Square and multiple logistic regression. The results of bivariate analysis showed a relationship between age (p=0.000), gender (p=0.002), and smoking habits (p=0.011) on hypertension. The results of multivariate analysis showed that there was a relationship between age (p=0.000, POR 4.12; 95% CI 3.07-5.56) and gender (p=0.021; POR 1.64; 95% CI 1.08-2 ,49) to hypertension. Conclusion: there is no relationship between lifestyle and hypertension. Age > 41 years has a 4.12 times greater chance of developing hypertension after controlling for smoking habits. Suggestion: Groups at risk apply a healthy lifestyle.